2022
DOI: 10.3390/ph15080930
|View full text |Cite
|
Sign up to set email alerts
|

Pumpkin Seed Oil-Loaded Niosomes for Topical Application: 5α-Reductase Inhibitory, Anti-Inflammatory, and In Vivo Anti-Hair Loss Effects

Abstract: Pumpkin seed oil (PSO)-loaded niosomes were prepared from Tween 20 and cholesterol by ethanol injection. Confocal microscopy showed better skin permeation and hair follicle accumulation of the niosomes compared to the PSO solution. The PSO-loaded niosomes inhibited 5α-reductase activity in DU-145 cells and hindered IL-6 activity in RAW 264.7 cells. These effects indicated the great potential of PSO-loaded niosomes to reduce hair loss. The hair scalp serum with PSO-loaded niosomes did not show irritation to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…CBD extract and CBD-NLCs with concentrations showing cell viabilities of higher than 80% were incubated with RAW264.7 cell macrophages as previously described by Teeranachaideekul et al [ 29 ] with some modifications. The cells were plated in a 24-well plate at a concentration of 1 × 10 5 cells/well and incubated at 37 °C under 5% CO 2 for 24 h. After that, the culture medium was removed and replaced with fresh culture medium containing test samples for 2 h. Then, 1 µg/mL lipopolysaccharide (LPS) was added to each well for 24 h of incubation at 37 °C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBD extract and CBD-NLCs with concentrations showing cell viabilities of higher than 80% were incubated with RAW264.7 cell macrophages as previously described by Teeranachaideekul et al [ 29 ] with some modifications. The cells were plated in a 24-well plate at a concentration of 1 × 10 5 cells/well and incubated at 37 °C under 5% CO 2 for 24 h. After that, the culture medium was removed and replaced with fresh culture medium containing test samples for 2 h. Then, 1 µg/mL lipopolysaccharide (LPS) was added to each well for 24 h of incubation at 37 °C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…RAW264.7 cell macrophages treated with and without LPS were used as positive and negative controls, respectively. Diclofenac sodium at the concentration of 1000 μM was used as a standard anti-inflammatory agent [ 29 ]. The concentration of IL-6 in culture media was determined using ELISA MAX TM Standard Set Mouse IL-6 (Biolegend, California, USA) according to the manufacturer’s instructions in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…The modulation of the SRD5A gene expression was observed in prostate tumor cells as previously described [ 10 ]. The DU-145 cells were used as an in vitro cell model to determine the expression of 5α-reductase for anti-hair loss applications [ 100 , 101 , 102 ] because the action of 5α-reductase was obviously evaluated in prostate cells [ 103 ]. Total RNA was isolated from the DU-145 cells treated with samples (RBO, 0.25 mg/mL; DFRB, 0.50 mg/mL; and H, 0.10 mg/mL) or SRD5A enzyme inhibitors (dutasteride and finasteride at a concentration of 0.10 mg/mL) for 24 h. The RNA extraction process was performed using the E.Z.N.A.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that the intake of PUFA in these seeds favors the improvement of the oxidant state and a hypotriglyceridemic effect ( 155 ). A study showed that pumpkin seed oil-loaded niosomes displayed a decrement in in vivo hair loss of 44.42%, representing 1.4-fold higher than commercial treatments ( 156 ). Authors also evaluated the cellular antiinflammatory activity of the experimental material, finding that functionalized niosomes inhibited 5α-reductase activity and hindered IL-6 activity in DU-145 and RAW 264.7 cellular models, respectively ( 156 ).…”
Section: Micronutrientsmentioning
confidence: 99%